2013
DOI: 10.1097/bot.0b013e31826f8cb9
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Results After Bone Grafting and K-Wire Fixation for Scaphoid Nonunion Surgery in Skeletally Immature Patients

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…We disregarded nonbiological surgical techniques (Reigstad et al, 2013) and opted for a vascularized procedure, owing to our patient's grave clinical scenario (nonunion D4 12 ), which was characterized by both avascular necrosis of the proximal pole and nonunion that had persisted beyond four years, both significant predictors of a poor functional outcome (Bae, Gholson, Zurakowski, & Waters, 2016;Moon, Dy, Derman, Vance, & Carlson, 2013. This condition required both angiogenic and vascular resources (Bae et al, 2016;Moon et al, 2013;Sunagawa, Bishop, & Muramatsu, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We disregarded nonbiological surgical techniques (Reigstad et al, 2013) and opted for a vascularized procedure, owing to our patient's grave clinical scenario (nonunion D4 12 ), which was characterized by both avascular necrosis of the proximal pole and nonunion that had persisted beyond four years, both significant predictors of a poor functional outcome (Bae, Gholson, Zurakowski, & Waters, 2016;Moon, Dy, Derman, Vance, & Carlson, 2013. This condition required both angiogenic and vascular resources (Bae et al, 2016;Moon et al, 2013;Sunagawa, Bishop, & Muramatsu, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Though most pediatric scaphoid fractures have a good prognosis with conservative management (Weber, Fricker, & Ramseier, ), scaphoid nonunion has been reported (Ahmed, Ashton, Tay, & Porter, ; Behr et al, ; Elhassan & Shin, ; Reigstad, Thorkildsen, Grimsgaard, Reigstad, & Rokkum, ). Since this lesion is a rarity, however—with a nonunion rate of just 0.8% (Elhassan & Shin, )—management experience is limited and optimal treatment remains controversial (Elhassan & Shin, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Studies revealed an incidence of 0.4 per 100,000 females and 2 per 100,000 males. [41][42][43] An 8-year observation of discharge data revealed an incidence of 3 per 100,000 females and 39 per 100,000 males. 42,43 Pediatric scaphoid fractures usually occur at 11 to 15 years of age, 1,2,7,13,14,17,23 but fractures have been reported as early as 4 years, though not identified until years later.…”
Section: Epidemiology Of Scaphoid Fracturesmentioning
confidence: 99%